Social and Cultural Relations in the Grand Duchy of Lithuania. Microhistories, ed. by Richard Butterwick, Wioletta Pawlikowska, Routledge Research in Early Modern History, Routledge, New York–Abingdon, 2019, xii + 257 pp., 5 tables - Frost, Robert (Studia Geohistorica, 2022)
Social and Cultural Relations in the Grand Duchy of Lithuania. Microhistories, ed. by Richard Butterwick, Wioletta Pawlikowska, Routledge Research in Early Modern History, Routledge, New York–Abingdon, 2019, xii + 257 pp., 5 tables